Kinetics and Mechanism of Hydrolysis of Mono-2-chloro- 5-nitroaniline Phosphate viaConjugate Acid Species - SINGH, M.K.; SHINDE, C.P. (Asian Journal of Chemistry, 2010)
Kinetic study of mono-2-chloro-5-nitroaniline phosphate has been made in acid region (0.1 to 7.0 mol dm-3) at 60 ºC. The log rate profile has a rate maximum at 4.0 mol dm-3. Ionic strength data upto 3.0 μ requires participation of conjugate acid species and to determine theoretical rates. Theoretical rates, estimated from second empirical term of Debye-Huckel equation, have been found in close agreement with experimental rates. Bimolecular behaviour has been decided by the Arrhenius parameters and by the analysis of molecularity data. The monoesters involves, P-N bond fission which is strengthened by comparative kinetic data.